PENERAPAN LITERASI PERPAJAKAN PADA USAHA MIKRO KECIL MENENGAH MACA COFFEE - Alvan, Muhammad; Fadhillah, Nurdatul; Silmi, Silmi (Ensiklopedia Sosial Review, 2024)
This practicum is motivated by observation data which shows the learning outcomes obtained in semester 3 which are applied to practicum activities in semester 4. The research aims to find out how much tax will be paid by the companies or MSMEs under study, and we can calculate how much tax by the amount of income that can be obtained from our MSMEs. Because tax is mandatory for people with income, such as MSMEs, which we studied in the current semester, which have certain provisions for making the payment. By taking a tax practicum course we can find out the procedures for paying taxes and the amount of tax that will be paid to an MSME each year.